Overcome Challenge Digital Literacy Of UMKM Garment Industry Through Approach Collaborative And Technology Simple : Study CST UMKM Case - Sherlita Mentari Changgriawan; Ellya Zulaikha (UNIVED Press, 2025)
Small and Medium Enterprises (SMEs) in Indonesia, particularly in the garment sector, hold great potential but face significant challenges in technology adoption. This study aims to identify the right digitalization strategy for CST Garment SMEs, focusing on the issue of low digital literacy. Using a Design Thinking approach, the research analyzes challenges and stakeholder needs, proposing solutions based on empirical data from observations and in-depth interviews. The findings show that implementing simple technologies like Google Sheets, CamScanner, and Google Drive improved efficiency by 88.88%, reduced reliance on manual systems, and enhanced data accuracy. Meanwhile, digital marketing testing through Instagram demonstrated a reach of 67,100 and increased followers from 0 to 1,148, proving the effectiveness of digital marketing in expanding market reach. This research proposes strategic steps for SMEs to tackle digitalization challenges: 1) Identifying catalysts for digitalization, 2) A personalized approach based on SME capacity, 3) Collaboration with stakeholders to develop relevant solutions, 4) Gradual implementation with project management, and 5) Continuous evaluation and success measurement. The study highlights the need for developing a digitalization evaluation framework for SMEs and policies supporting digital adoption. Further research is required to explore success factors in garment SME digitalization in Indonesia.